NELA.03Laparoscopy in Emergency Surgery is Associated with Lower Risk-Adjusted Mortality. (28th October 2021) - Darbyshire, Alexander; Kostakis, Ina; Pucher, Phil; Prytherch, David; Toh, Simon; Mercer, Stuart
Abstract: Aims: To compare risk-adjusted outcomes after emergency intestinal surgery by operative approach. Methods: Data from December 2013-November 2018 was retrieved from the NELA national database. Complete data on 102, 154 patients with P-POSSUM was available, and 47, 667 had NELA score. AUROC curves were calculated to assess model discrimination (c-statistic), and calibration plots to visualise agreement between predicted and observed mortality.  Standardised Mortality Ratio's (SMR) were calculated for the total cohort and by operative approach. Operative approach was divided into: laparotomy, completed laparoscopically, converted to open and lap assisted. Results: Both P-POSSUM and NELA score displayed good discrimination for total cohort and by operative approach (P-POSSUM c-statistic=0.801-0.815; NELA score c-statistic=0.851-0.880).  Calibration plots demonstrated that P-POSSUM was highly accurate up to 20% mortality, after which it substantially over-predicted mortality.  NELA score was highly accurate up to 25% mortality after which it slightly under-predicted. Overall SMR of observed vs expected deaths was 0.77 using P-POSSUM, 0.8 for laparotomy and 0.46 for laparoscopy.  Restricting cases to < 10% predicted mortality (n = 65, 000), overall SMR improved (0.9) and was considerably lower for cases completed laparoscopically (0.41) compared to open (0.97).  Using NELA scores of < 10% predicted mortality (n = 27, 000) had similar overall SMR (0.96), with cases completed laparoscopically displaying much lower SMR (0.61) compared to laparotomy (1.0). Conclusions: SMR's calculated using P-POSSUM and NELA score have demonstrated that laparoscopy has significantly lower observed vs expected mortality rate compared to laparotomy. This raises the question of why laparoscopy is associated with reduced mortality and should operative approach be included in risk models?